2015
DOI: 10.1016/j.ijsu.2015.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Is laparoscopic treatment of incisional and recurrent hernias associated with an increased risk for complications?

Abstract: Laparoscopic treatment of complex hernias as incisional hernias, recurrent hernias and hernias with interenteric and enteroperitoneal adhesions is associated with high rates of minor and major complications. A high level of expertise of the surgeon and the camera-guiding assistant is therefore needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
6
0
1
Order By: Relevance
“…In a comparative study on laparoscopic treatment of 64 primary vs. 34 recurrent incisional hernia significantly more major complications were documented (12.5 vs. 17.6%) for the recurrent incisional hernia repair (40) (Table 1). With a median follow-up of 942 days (range 339–1693 days) the recurrence rate for primary incisional hernia repair was 11.0 vs. 26.5% for recurrent incisional hernia (40). “The authors concluded that laparoscopic treatment of recurrent incisional hernias was associated with high rates of minor and major complications (40).…”
Section: Case Series Of Laparoscopic Recurrent Incisional Hernia Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…In a comparative study on laparoscopic treatment of 64 primary vs. 34 recurrent incisional hernia significantly more major complications were documented (12.5 vs. 17.6%) for the recurrent incisional hernia repair (40) (Table 1). With a median follow-up of 942 days (range 339–1693 days) the recurrence rate for primary incisional hernia repair was 11.0 vs. 26.5% for recurrent incisional hernia (40). “The authors concluded that laparoscopic treatment of recurrent incisional hernias was associated with high rates of minor and major complications (40).…”
Section: Case Series Of Laparoscopic Recurrent Incisional Hernia Repairmentioning
confidence: 99%
“…With a median follow-up of 942 days (range 339–1693 days) the recurrence rate for primary incisional hernia repair was 11.0 vs. 26.5% for recurrent incisional hernia (40). “The authors concluded that laparoscopic treatment of recurrent incisional hernias was associated with high rates of minor and major complications (40). Therefore, the surgeon needs to have a high level of expertise” (40).…”
Section: Case Series Of Laparoscopic Recurrent Incisional Hernia Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative seroma formation is a frequent event (up to 10%), while true hematomas are also a reported occurrence [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, laparoscopic incisional and ventral hernia repair (LIVHR) may represent an alternative to open surgery, avoiding wide recissions and accelerating postoperative return to normal activities. Despite a large number of encouraging papers, reviews, international guidelines [3][4][5][6][7][8][9] a meta-analysis [10] and a Cochrane review [11] suggested that LIVHR could be superior to the open approach; other works have reported equivalent/ inferior results or narrow indications [12][13][14][15]. Moreover, a major concern is which type of mesh is to be employed.…”
Section: Introductionmentioning
confidence: 99%